EFFECT OF FOLIAR APPLICATION OF UREA ON DIFFERENT GROWTH STAGES OF WHEAT - Veesar, Siraj Ahmed; Laghari, Ghulam Mustafa; Ansari, Muhammad Ali; Oad, F C; Soomro, Aijaz Ahmed (LIFE: International Journal of Health and Life-Sciences, 2017)
The experiment was conducted at Student Farm, Department of Agronomy, Sindh Agriculture University, Tandojam during the year 2012-13, to evaluate the effect of foliar dose of urea on different growth stages of wheat variety TJ-83 with 3 replications, experimental design Randomized Block Design with two factors A foliar nitrogen concentration of urea with treatments control (non -treated plots), 0.5% and 1.0%however in factor B include two growth stages i.e. Tillering stage, Anthesis stage. Wheat variety TJ-83 was cultivated at net plot size 4x4= (16 m2). The results revealed that germination (%) showed non-significant response to foliar nitrogen concentrations, growth stages and their interaction whereas all other wheat traits significantly affected by different foliar fertilizers, growth stages and their interaction.The mean maximum plant height (cm), grains spike-1 and seed index (1000 grain weight g) were recorded at 0.5% urea nitrogen concentrations whereas other wheat traits tillers plant-1, spike length (cm), spikelets spike-1 and grain yield kg ha-1 were foundThe experiment was conducted at Student Farm, Department of Agronomy, Sindh Agriculture University, Tandojam during the year 2012-13, to evaluate the effect of foliar dose of urea on different growth stages of wheat variety TJ-83 with 3 replications, experimental design Randomized Block Design with two factors A foliar nitrogen concentration of urea with treatments control (non -treated plots), 0.5% and 1.0%however in factor B include two growth stages i.e. Tillering stage, Anthesis stage. Wheat variety TJ-83 was cultivated at net plot size 4x4= (16 m2). The results revealed that germination (%) showed non-significant response to foliar nitrogen concentrations, growth stages and their interaction whereas all other wheat traits significantly affected by different foliar fertilizers, growth stages and their interaction.The mean maximum plant height (cm), grains spike-1 and seed index (1000 grain weight g) were recorded at 0.5% urea nitrogen concentrations whereas other wheat traits tillers plant-1, spike length (cm), spikelets spike-1 and grain yield kg ha-1 were found superior at 0.5% and 1.0% foliar nitrogen concentrations.Maximum mean for growth stages was observed at plant height (cm), tillers plan-1,spike length (cm), spikelets spike-1, seed index (1000 grain weight g) and grain yield were recorded at tiilering stages whereas higher value of grains spike-1 was recorded at anthesis growth stage of wheat. The interactive results indicated that the maximum plant height (cm) was recorded at interaction of 1.0% foliar nitrogen concentration x tillering stage, however higher values of tillers plan-1, spike length (cm) spikelets spike-1, seed index (1000 grain weight g) and grain yield kg ha-1 were observed at interaction of 0.5% and 1.0% foliar nitrogen concentrations x tillering stages. Further results indicated that the foliar nitrogen concentrations, growth stages and their interaction showed enhanced values as compared to control plots where no any fertilizer was applied.